‘Where is the safe space?!’ From drag queen storytime to LGBTQA+ inclusive practice - Chen, Julian; Cumming-Potvin, Wendy; Andreassen, Kim; McKenzie, Bri (2024)
Drag queen storytime (DQS), also known as drag (queen) story-hour, has been implemented in selected libraries and schools across North America, Oceania, and the United Kingdom, to open safe spaces for drag queens to read children’s books that may involve LGBTQA+ characters or subject matters. Unfortunately, despite its popularity with many children and families, DQS has faced intense public protests regarding the perceived LGBTQA+ themed texts, and violent threats against the performers and organisers. Underpinned by queer, transgender, and feminist theory as well as intersectionality, this creative essay probes the current affairs of DQS as it relates to LGBTQA+ human rights. As a platform to highlight LGBTQA+ digital, visual, and print texts, this essay channels the authors’ ‘inner drags’ and draws on queer narrative inquiry to critically reflect and face our own fear and vulnerability in professional and queer undertaking. Using a recent DQS incident as a case in point, we demonstrate how unleashing our inner queerness through drag can empower us as queer academics and allies to counter ‘dragphobia’ and celebrate gender and sexuality diversity. This creative work aspires to provide provocations for further exploration of queer inclusivity across social, cultural, and political intersections, with the intent to promote LGBTQA+ inclusive practices.